Protecting Victims of Human Trafficking from Liability: An Evaluation of Section 45 of the Modern Slavery Act. (October 2019) - Muraszkiewicz, Julia
The evolution of protective measures offered to victims of human trafficking at a European regional level has begun to have an impact at a national level. In this article, the author explores a provision intended to guard victims of human trafficking, who have been compelled to commit crimes, against prosecution and punishment. The provision under scrutiny is the statutory defence found in s 45 of the Modern Slavery Act, 2015 (England and Wales). The article draws on the obligations spelt out in regional law (the 2005 Council of Europe Convention on Action Against Trafficking in Human Beings and Directive 2011/36 on preventing and combating trafficking in human beings and protecting its victims ) and asks if England and Wales fulfil their duties with respect to protecting trafficked persons from being prosecuted and punished.